Development of a Filament Extruder Using Flow Theory with the Newtonian Fluid Assumption - Nguyen, Nien Thi; Truong Van, Chinh; Khoa Nguyen, Trieu (International Journal of Integrated Engineering, 2023)
This article presents an investigation of the flow characteristics of the polymer melt in a single-screw extruder and the design of a filament extruder to verify the above theory. The flow characteristics of the polymer melt in a single-screw extruder are likable to that of a viscous liquid between two infinitely parallel sheets, one moving and the other stationary. An integrated flow equation was then found for a case when the viscosity of a liquid remains constant in an isothermal extrusion. These flow behavior theories were then verified via the design and fabrication of a filament extruder for 3D printers.